2013
DOI: 10.1161/strokeaha.111.000522
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Coupling Inhibitory and Facilitatory Repetitive Transcranial Magnetic Stimulation to Enhance Motor Recovery in Hemiplegic Stroke Patients

Abstract: the potential for a consecutive suppressive-facilitatory TMS protocol to improve motor outcomes after chronic stroke. Methods-Fifty-four chronic hemiplegic stroke patients were allocated across 4 groups to undergo 20 daily sessions of (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(94 citation statements)
references
References 38 publications
6
82
1
5
Order By: Relevance
“…One of the prevailing models of motor recovery in ischaemic stroke is compensatory excitation of the contralesional hemisphere that is causing pathological disinhibition of transcallosal pathways 135 . Consequently, concurrent stimulation of the lesioned hemisphere and inhibition of the non-lesioned hemisphere (that is, through the use of TMS) may have beneficial effects on recovery 136 . Active patient participation in the therapy is another guiding principle of rehabilitation that is derived from studies employing forced use of the affected limb 137 and robotic therapy that minimizes assistance to encourage greater patient effort 138 .…”
Section: Rehabilitation In Strokementioning
confidence: 99%
“…One of the prevailing models of motor recovery in ischaemic stroke is compensatory excitation of the contralesional hemisphere that is causing pathological disinhibition of transcallosal pathways 135 . Consequently, concurrent stimulation of the lesioned hemisphere and inhibition of the non-lesioned hemisphere (that is, through the use of TMS) may have beneficial effects on recovery 136 . Active patient participation in the therapy is another guiding principle of rehabilitation that is derived from studies employing forced use of the affected limb 137 and robotic therapy that minimizes assistance to encourage greater patient effort 138 .…”
Section: Rehabilitation In Strokementioning
confidence: 99%
“…When applied over the ipsilesional motor cortex of chronic stroke patients, reaction time and pinch force of the affected hand improved (Hummel et al, 2006). Similarly, facilitatory repetitive TMS (rTMS) applied to the ipsilesional hemisphere (Khedr et al, 2010) and inhibitory rTMS targeting the contralesional hemisphere (Takeuchi et al, 2005) or their combination (Sung et al, 2013) showed effects on motor functions in stroke, but more studies with larger sample sizes are needed (Hao et al, 2013).…”
Section: Combination Of Bmis and Brain Stimulation In Neurorehabilitamentioning
confidence: 99%
“…This was demonstrated to be both safe and effective in boosting motor facilitating efficacy compared with traditional 10-session rTMS. 29 However, a safe, optimal repetition number, and appropriate rest interval for aphasic patients remains uncertain. With regard to this combined therapy, establishment of an optimal conditioning protocol is important, and further dosage studies should be conducted.…”
mentioning
confidence: 99%